(untitled) (Iranian Journal of Kidney Diseases, 2014)
Ciprofloxacin is a commonly used antibiotic. Renal side effects are rare and are usually immune mediated. Clinical and experimental studies have suggested that crystalluria and crystal nephropathy occur in alkaline urine. Preexisting kidney function impairment, high dose of the medication, and advanced age predispose to this complication. We report a case of crystal nephropathy in a young woman treated with ciprofloxacin and a nonsteroidal anti-inflammatory drug.